Effect of the Addition of Sikacrete-W and Viscocrete-3115n on the Compressive Strength of Concrete in Waterlogged Bore Pile Casting Work - Abun Bunjamin; Ayu Ningrum Pertiwi; Elpan Yudiana; Muhammad Makkih; Laode Azan Muzahab (Journal of Social Research, 2025)
This study examines the effect of the addition of Sikacrete-W and Viscocrete-3115N additives on the compressive strength of concrete in waterlogged bore pile casting work. Concrete is an important construction material, but underground casting can lead to washout and segregation, which negatively impacts concrete quality. In this study, variations of Sikacrete-W addition of 3%, 5%, and 10% and 0.6% Viscocrete-3115N were used to improve the cohesion and viscosity of the mixture. The test results showed that the average compressive strength of concrete with the addition of additives was lower than that of normal concrete, with the largest decrease occurring in the 10% Sikacrete-W mixture. Meanwhile, a 5% Sikacrete-W mixture yielded an optimal compressive strength of 31.74 MPa, suggesting that the addition of additives could affect the characteristics of concrete under special conditions.